2020
DOI: 10.1002/kjm2.12303
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of hepatitis C virus preserve liver function and prolong survival in advanced hepatocellular carcinoma patients with limited life expectancy

Abstract: Whether patients with advanced hepatocellular carcinoma (aHCC) benefit from hepatitis C virus (HCV) eradication is uncertain. We aimed to investigate whether a survival benefit was conferred by HCV eradication in aHCC patients. This retrospective cohort study enrolled 168 HCV‐infected aHCC patients from April 2013 to January 2019. All patients were treated with sorafenib. Endpoints included overall survival (OS), progression free survival (PFS), and time to liver decompensation. Patients with undetectable HCV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…As previously noted, prior studies focused on the effect of anti-HCV therapy after HCC developed and have shown improved liver-related and overall survival [ 11 , 17 , 22 , 23 , 24 ], but little is known about the long-term outcome among patients with post-SVR HCC. In the current study, we observed that patients with post-SVR HCC had better survival than the patients who developed HCC while having HCV viremia.…”
Section: Discussionmentioning
confidence: 99%
“…As previously noted, prior studies focused on the effect of anti-HCV therapy after HCC developed and have shown improved liver-related and overall survival [ 11 , 17 , 22 , 23 , 24 ], but little is known about the long-term outcome among patients with post-SVR HCC. In the current study, we observed that patients with post-SVR HCC had better survival than the patients who developed HCC while having HCV viremia.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study for HCC patients in BCLC stage B, the median patient survival time was significantly longer in DAA-treated patients, when compared to that in DAA-untreated patients (40.1 vs. 22.9 months) [26]. Moreover, in a retrospective cohort study for HCC patients in BCLC stage C, whose HCCs were treated with sorafenib, HCV eradication through DAA therapy also confirmed patient survival benefits [27]. However, not all studies demonstrated patient survival benefits as coming from DAA therapy for patients with unresectable HCCs [9].…”
Section: Discussionmentioning
confidence: 96%
“…This study found that treatment with DAAs was highly effective in eradicating HCV in patients with a history of HCC, despite their being older and more likely to have liver fibrosis and diabetes mellitus than patients without a history of HCC. DAAs are also effective in patients with advanced HCC[ 22 - 24 ]. HCV eradication by DAAs ameliorates liver inflammation and suppresses liver fibrosis progression, preserving or improving liver function.…”
Section: Discussionmentioning
confidence: 99%